HUBUNGAN TINGKAT STRES DENGAN SIKLUS MENSTRUASI PADA MAHASISWI STIT DINIYYAH PUTERI KOTA PADANG PANJANG - Vetri Nathalia (Menara Ilmu, 2019)
Ideally scheduled menstrual cycle every month with span of time between 21-35 days each time of menstrual period. The irregular menstrual cycle shows irregularities in the metabolic and hormonal systems. This cycle difference is determined by several factors: stress. Where stress is the cause of menstrual disorders. The purpose of this research is to know the distribution of Frequency of stress level with menstrual cycle at student of Tarbiyah High School (STIT) Diniyyah Puteri Rahmah El Yunusiyyah Padang Panjang. This research used descriptive correlation method using Cross-Sectional Study design. The research was conducted at Tarbiyyah School of Science (STIT) Diniyyah Puteri Rahma El Yunusiyyah Padang Panjang in January 2017. Popoulasi in this research is all student of Tarbiyah High School (STIT) Diniyah Rahmah El Yunusiyyah Padang Panjang. The sample in this study amounted to 89 people. Data management is done by computerized using SPSS program with univariate and bivariate analysis, statistic test used is Chi-square. Univariate analysis showed that 60% of respondents had mild stress and 67.4% of respondents had abnormal menstrual cycles. The result of statistical test of bivariate analysis obtained p value = 0,000 which means there is relationship of stress level with menstrual cycle. It is advisable for female students to be more open in facing problems and obstacles in lecturing process so as to help reduce stress burden felt by student. Keywords: stress, menstruation cycle